Caracterização etnopedológica em um cambissolo eutrófico em diferentes usos agropecuários na Chapada do Apodi - Souza, Rauny Oliveira de (Universidade Federal Rural do Semi-Árido, 2014)
The integration of popular knowledge and scientific forms as an essential tool in the identification of appropriate practices for soil and agricultural uses for its conservation management. This study aimed to characterize the attributes of soil from agricultural scientific and Ethnopedological the Projeto de Assentamento Terra de Esperança study uses located at Governador Dix-Sept Rosado - RN, located in the middle region of the western Rio Grande do Norte, in microregion of the Chapada do Apodi. The survey was conducted from September 2013 to May 2014, the physical and chemical soil attributes were analyzed in the following locations: Native Forest Area (AMN), Orchard Cajaraneiras (APM), Collective Conventional Cultivation Area (AC) and area of colluvium (ACol). Sample collection at depths of were performed 0,00 0,10; 0,10 0,20; 0,20 0,30 m, benefited the Laboratory of Analysis of Soil Water and Plant - LASAP/DCAT/UFERSA. Particle size, particle density, soil consistency, mechanical resistance to root penetration and chemical attributes: EC, pH, TOC, P, K, Na, Ca, Mg, H + Al, CEC at pH 7,0 the physical attributes were evaluated, effective CEC, SB and V. Multivariate analyzes were used as the main tool, specifically the Principal Component Analysis, to distinguish the areas surveyed in terms of potential and / or restrictions of the environment. Ethnopedological studies and learning workshop with (the) farmers (as) were performed and built concepts of soil attributes (exposure images of crops, soil color, soil consistency, microbiological activity and infiltration test), the landscape, weather patterns and agricultural production cycles depending on the experience of the group. Description of the soil popular way according to the Brazilian Classification System soil profile was performed in addition to the mineralogical analysis of samples from the profile horizons. It was observed that the first factor generated for the attributes of the areas surveyed explained 48.33% of the total variation of the studied attributes and the highest correlation coefficients (≥ | 70 |) variables were identified: sand, silt, pH, Ca2+, (H + Al), SB, t, T, V in the layer 0.00 - 0.10 m. These attributes were more sensitive to distinguish the areas of agricultural uses, being observed in the projection vectors, where the attributes have become more distant from the axis of factor 1 diagram. There was integration of popular and scientific knowledge in research on the adoption of appropriate practices to local particularities and the construction of essential concepts for the conservation of natural resources. The soil classification was scientifically Eutrophic Cambisol Ta typical and popular classification as dark clay surface and "white clay" or "gravel" in the subsurface
Ethnopedological characterization in an eutrophic Cambisol in different agricultural uses in Chapada do Apodi
Keywords: Soil Science; Ethnoscience; Governador Dix-sept Rosado/RN; Semiárid; Ciência do solo; Etnociência; Governador Dix-Sept Rosado/RN; Semiárido; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO